Microarray gene expression profiling and analysis of bladder cancer supports the sub‐classification of T1 tumours into T1a and T1b stages. (31st October 2013) - Descotes, Françoise; Dessen, Philippe; Bringuier, Pierre Paul; Decaussin, Myriam; Martin, Pierre Marie; Adams, Marjorie; Villers, Arnauld; Lechevallier, Eric; Rebillard, Xavier; Rodriguez‐Lafrasse, Claire; Devonec, Marian; Paparel, Philippe; et al.
<x xml:space="preserve">Abstract</x> Objective To try and identify a molecular signature for pathological staging and/or grading. through microarray analysis. Patients and Methods We performed a prospective multicentre study between September 2007 and May 2008 that included 108 bladder tumours (45 pTa, 35 pT1 and 28>pT1). Microarray analysis was performed using Agilent Technologies Human Whole Genome 4 × 44K oligonucleotide microarrays (Agilent, Santa Clara, CA, USA). A 'dual colour' method was used vs a reference pool of tumours. From the lists of genes provided by the Biometric Research Branch class comparison analyses, we validated the microarray results of 38 selected differentially expressed genes using reverse transcriptase quantitative PCR in another bladder tumour cohort (n = 95). Results The cluster 'superficial vs invasive stage' correctly classified 92.9% of invasive stages and 66.3% of superficial stages. Among the superficial tumours, the cluster analysis showed that pT1b tumours were closer to invasive stages than pT1a tumours. We also found molecular differences between low and high grade superficial tumours, but these differences were less well defined than the difference observed for staging. Conclusions We confirmed that the histopathological classification into subgroups pTa, pT1a and pT1b can be translated into a molecular signature with a continuous progression of deregulation (overexpression or repression of these genes) from superficial (pTa) to more invasive (pT1a then b) stages.